Application of the inverse finite element method to design wind turbine blades. (1st February 2017) - Albanesi, Alejandro; Fachinotti, Victor; Peralta, Ignacio; Storti, Bruno; Gebhardt, Cristian
Abstract: This paper presents a novel methodology to design wind turbine blades using the Inverse Finite Element Method (IFEM). IFEM takes as domain of analysis the geometry of the blade after large elastic deformations caused by given service loads. The deformed shape of the blade is that determined to be efficient using an aerodynamics analysis. From this analysis, the aerodynamic loads on the blade are known. Then, we choose the materials to manufacture the blade. As usual, the blade is assumed to be made of multiple layers of composite materials. After materials selection, the stationary inertial loads on the blade are known. Finally, given the desired deformed shape and all the service loads, we use IFEM to compute the manufacturing shape of the blade. This is a one-step, one-direction strategy where the aerodynamics analysis feeds the structural (IFEM) analysis, and no further interaction between both solvers is required. As an application of the proposed strategy, we consider a medium power 40-KW wind turbine blade, whose whole design is detailed along this work.